The anti-landscape - Nye, David E., 1946-; Elkind, Sarah S., 1963- (Studies in Environmental Humanities, 2014)
There have always been some uninhabitable places, but in the last century human beings have produced many more of them. These anti-landscapes have proliferated to include the sandy wastes of what was once the Aral Sea, severely polluted irrigated lands, open pit mines, blighted nuclear zones, coastal areas inundated by rising seas, and many others. The Anti-Landscape examines the emergence of such sites, how they have been understood, and how some of them have been recovered for habitation. The anti-landscape refers both to artistic and literary representations and to specific places that no longer sustain life. This history includes T. S. Eliot's Wasteland and Cormac McCarthy's The Road as well as air pollution, recycled railway lines, photography and landfills. It links theories of aesthetics, politics, tourism, history, geography, and literature into the new synthesis of the environmental humanities. The Anti-Landscape provides an interdisciplinary approach that moves beyond the false duality of nature vs. culture, and beyond diagnosis and complaint to the recuperation of damaged sites into our complex heritage. This is the first volume in the new series Studies in Environmental Humanities .